Archaeological Research in Estonia 1865-2005 - Lang, Valter (Estonian Archaeology, 2006)
This volume is dedicated to the historiography and analysis of the present state of Estonian archaeology. Part I (articles by Valter Lang and Marge Konsa) provides a review of the general development of archaeological research in Estonia from the 19th century to the beginning of the 21st century, focusing on institutional changes and advances in theoretical thinking and approaches. Part II includes articles by Aivar Kriiska, V. Lang, Andres Tvauri, Heiki Valk, Ain Mäesalu, Anton Pärn, Erki Russow and Arvi Haak on the previous research into the prehistoric and historical periods. In Part III, A. Tvauri and Mauri Kiudsoo discuss the formation and present situation of the archaeological and numismatic collections, and the establishment and development of archaeological heritage protection. Part IV discusses some more specific areas of research in Estonian archaeology, such as application of methods from the natural sciences in archaeology (A. Kriiska), settlement archaeology (V. Lang), underwater archaeology (Maili Roio), and connections between archaeology and oral tradition (H. Valk).